Precipitation in July maximizes total above-ground productivity of the desert steppe in Inner Mongolia, China - Han, Chunxue; Li, Ruichao; Li, Haigang (PloS one, 2024)
Precipitation distribution during the growing season and interannual precipitation variation may have significant impacts on grassland ecosystem productivity at the site level. To explore the effect of the distribution of precipitation on plant communities in the Inner Mongolian desert steppe dominated by Stipa breviflora , we analyzed monthly precipitation patterns during the growing season (May–October) over the past 60 years (1961–2020) and identified four major precipitation distribution patterns. These included the concentrated precipitation during July (TΛ7), August (TΛ8), and during the early and late growth stages. However, with precipitation being scarce during the boom (TM), the distribution resembled a normal distribution (T∩). Field experiments simulating the four distributions were conducted from May to October 2021. The results showed that the effects of the distribution of precipitation on plant species, diversity, and abundance were not significant; only the Pielou evenness showed a significant effect after July. The total above-ground net primary productivity (ANPP) of TΛ7 was 55.4% higher than those of the other three patterns, whereas the differences among the other three precipitation distributions were not significant. The annual forb Neopallasia pectinate was the primary contributor to the increased ANPP of TΛ7. These results suggest that the S . breviflora desert steppe achieved maximum productivity when the precipitation reached 41.6% of the annual average during July and satisfied the basic plant growth requirements during other months. This study emphasizes the implementation of management measures (irrigation or artificial precipitation) for maximizing forage yield and forecasting the plant composition in desert steppes.